2015
DOI: 10.1007/s10544-015-9999-9
|View full text |Cite
|
Sign up to set email alerts
|

Early prognosis of metastasis risk in inflammatory breast cancer by texture analysis of tumour microscopic images

Abstract: Inflammatory breast cancer (IBC) is a rare and aggressive type of locally advanced breast cancer. The purpose of this study was to determine the value of microscopic tumour histomorphology texture for prognosis of local and systemic recurrence at the time of initial IBC diagnosis. This retrospective study included a group of 52 patients selected on the basis of non-metastatic IBC diagnosis, stage IIIB. Gray-Level-Co-Occurrence-Matrix (GLCM) texture analysis was performed on digital images of primary tumour tis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 36 publications
(42 reference statements)
3
8
0
Order By: Relevance
“…Descriptive statistics and standard clinicopathological prognostic factors are not shown as these were already described for both patient groups used in this study (Kolarevic et al ., , Vujasinovic et al ., ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Descriptive statistics and standard clinicopathological prognostic factors are not shown as these were already described for both patient groups used in this study (Kolarevic et al ., , Vujasinovic et al ., ).…”
Section: Resultsmentioning
confidence: 99%
“…Descriptive statistics and standard clinicopathological prognostic factors are not shown as these were already described for both patient groups used in this study (Kolarevic et al, 2015, Vujasinovic et al, 2015b. Image preprocessing by use of six algorithms was followed by image analysis using five different GLCM, two monofractal and ten multifractal algorithms.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…LARC locally advanced rectal cancer, pCR pathological complete response, T2WI T2-weighted imaging, VOI volume of interest, IVIM-DWI intravoxel incoherent motion diffusion-weighted imaging, nCRT neoadjuvant chemoradiotherapy, TRG tumor regression grade generated from dynamic contrast-enhanced MRI images report can discriminate between the cured and relapsed cervical cancer patients who underwent chemoradiotherapy, whereas the first-order features cannot [38]. These observations imply the advantage of GLCM analysis over the firstorder statistics in discriminating the pathological response of LARC, which may be because the first-order texture features do not provide spatial information of images and therefore they cannot provide sufficient information on tumor heterogeneity [17,33,34,39].…”
Section: Discussionmentioning
confidence: 99%
“…These findings revealed that baseline GLCM features derived from IVIM-DWI could act as imaging predictors of pCR in patients with LARC. Among these GLCM features, Correlation and SumAverg are not directly related to heterogeneity, whereas Contrast and DifVarnc are measures of tissue heterogeneity [39], that is to say, lower Contrast or DifVarnc means less heterogeneity [35,36,39,40]. In the present study, all the values of Contrast and Dif-Varnc derived from the ADC, D, and D* maps in the pCR group were lower than those in the non-pCR group, implying that higher heterogeneity on IVIM-DWI maps may be associated with poorer therapeutic effect.…”
Section: Discussionmentioning
confidence: 99%